2013
DOI: 10.1104/pp.113.225680
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Cyclic Nucleotide-Gated Ion Channels AtCNGC2 and AtCNGC4 Work in the Same Signaling Pathway to Regulate Pathogen Defense and Floral Transition      

Abstract: Arabidopsis (Arabidopsis thaliana) cyclic nucleotide-gated ion channels (CNGCs) form a large family consisting of 20 members and have been implicated in Ca 2+ signaling related to various physiological processes, such as pathogen defense, development, and thermotolerance. The null mutant of AtCNGC2, defense, no death (dnd1), exhibits autoimmune phenotypes, while it is impaired in mounting the hypersensitive response, which is a hallmark of effector-triggered (i.e. RESISTANCE-gene mediated) resistance. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 51 publications
(111 reference statements)
4
137
3
Order By: Relevance
“…It is therefore tempting to assume a possible regulation of the SA‐dependent pathway by cAMP through cytosolic Ca 2+ homeostasis modulation. Much evidence indicates that cAMP permits Ca 2+ entrance into plant cells through CNGCs, initiating that the signalling event cascades occurred in response to biotic stress (Clough et al ., ; Balagué et al ., ; Jurkowski et al ., ; Yoshioka et al ., ; Ali et al ., ; Chin et al ., ; Lu et al ., ). Our data suggested that the delay in HR activation could be in part due to a failure in the activation of CNGCs in cAS plants, although we cannot exclude a possible downregulation of Ca 2+ efflux transporters in our system (Bose et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore tempting to assume a possible regulation of the SA‐dependent pathway by cAMP through cytosolic Ca 2+ homeostasis modulation. Much evidence indicates that cAMP permits Ca 2+ entrance into plant cells through CNGCs, initiating that the signalling event cascades occurred in response to biotic stress (Clough et al ., ; Balagué et al ., ; Jurkowski et al ., ; Yoshioka et al ., ; Ali et al ., ; Chin et al ., ; Lu et al ., ). Our data suggested that the delay in HR activation could be in part due to a failure in the activation of CNGCs in cAS plants, although we cannot exclude a possible downregulation of Ca 2+ efflux transporters in our system (Bose et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of null mutant of AtCNGC2 , defense , no death ( dnd1 ), display delayed PCD when challenged with pathogens [22]. Null mutants of AtCNGC4 (the closest paralog of AtCNGC2 ) exhibit remarkably similar phenotypes to dnd1 [62, 63], supporting a notion that AtCNGC2 and AtCNGC4 may form a heteromeric Ca 2+ channel complex [54]. Similarly, several recent studies also documented evidence for a role of AtCNGC11 and AtCNGC12 in PCD and plant immunity [21, 23, 24, 26].…”
Section: Discussionmentioning
confidence: 99%
“…AtCNGC2 was co-expressed with AtCNGC4 as the positive control [54]. For transient expression, the Agrobacterium tumefaciens strain EHA105 carrying the BiFC constructs were co-infiltrated into N .…”
Section: Methodsmentioning
confidence: 99%
“…A second class of potential Ca 2+ channels are the cyclic nucleotide gated channels (CNGCs). Their initial implication in plant defence response comes from mutant studies where the 'constitutive expresser of pathogenesis-related (PR) genes22 ' (cpr22) gene is the result of a genomic deletion creating an in-frame chimeric CNGC11-CNGC12 fusion (Yoshioka et al, 2006), or from the fact that the defence-no-death mutants, dnd1 and dnd2, are CNGC2 and CNGC4, respectively (Chin et al, 2013). Arabidopsis CNGC2/DND1 is implicated in the transduction of DAMP, Pep1, (Qi et al, 2010) and bacterial lipopolysaccharide (LPS)mediated reactions (Ali et al, 2007).…”
Section: Reviewmentioning
confidence: 99%